2009
DOI: 10.4103/1596-3519.55764
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of occupational hazards and utilization of safety measures among welders in kaduna metropolis, Northern Nigeria

Abstract: Background: Welders are exposed to a variety of occupational hazards with untoward health effects. However, little is known of welders' awareness of health hazards and their adherence to safety precautions in developing countries. This study assessed the awareness of occupational hazards and adherence to safety measures among welders in Kaduna metropolis in northern Nigeria. Methods: A structured questionnaire was administered on a cross-section of 330 welders in Kaduna metropolis in northern Nigeria. Informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
92
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(129 citation statements)
references
References 5 publications
(11 reference statements)
28
92
9
Order By: Relevance
“…The results of this study are consistent with previous research by Sabitu et al 5 that concluded that some of the effects of welding on health include photokeratitis or arc eye. This results was in accordance with the opinion of Davies 8 which concluded that welding emits a wide spectrum of radiations ranging between 200-1,400 nm.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of this study are consistent with previous research by Sabitu et al 5 that concluded that some of the effects of welding on health include photokeratitis or arc eye. This results was in accordance with the opinion of Davies 8 which concluded that welding emits a wide spectrum of radiations ranging between 200-1,400 nm.…”
Section: Discussionsupporting
confidence: 93%
“…Some variables that were partially related to photokeratoconjunctivitis were the duration of UV exposure (p=0.055) and the number of working days (p=0.037). The regression model can be written as follows: Y=a+b 1 .χ 1 +b 2 .χ 2 +b 3 .χ 3 +b 4 .χ 4 +b 5 .χ 5 +b 6 .χ 6 +e Y=6.476−0.169χ 1 +0.242χ 2 +0.32χ 3 −0.089χ 4 −0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study further shows that 82.3% workers used at least one protective equipment while working whereas the study by Sabitu K et al in Nigeria reported that only 34.2% of welders used one or more types of protective device. 7 This variation may be due to more awareness in the city.…”
Section: Discussionmentioning
confidence: 99%
“…7 The musculoskeletal pain is a major concern for 82.3% welders. This finding is higher than those conducted by Sabitu K et al and Burdorf A et al 5,7 The reason may be the poorer ergonomic conditions to which these workers are exposed to.…”
Section: Discussionmentioning
confidence: 99%